EFEKTIVITAS INFUSA RAMBUT JAGUNG (Zea mays L.) SEBAGAI ANTIDIABETES PADA MENCIT Swiss webster YANG DIINDUKSI DENGAN ALOKSAN - Anita Mursiany (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2019)
Diabetes mellitus is a dessease that can be suffered by all age. Besides that this dessease can be effect for the other organ. Corn hair is a waste that if not processed it can cause the occurrence of decay. Best on the last research corn hair contain flavonoid compounds which can use for antidiabetic. This research for knowing how the effectivity infusa of corn hair (Zea mays L.) for antidiabetic drug in mice.This research is experimental research for know the effectivity and comparison of dosage giving infusa of corn hair in Swiss webster mice. In this research use alloxan for induction of diabetes mellitus, acarbose for control positive and aquadest for control negative. Infusa of corn hair dose which give is 0,52 g/kgBB; 1,04 g/kgBB and 2,08 g/kgBB.The result of this research shows that infusa of corn hair can reduce blood sugar levels in Swiss webster mice. Dose infusa of corn hair 1,04 g/kgBB is the effective dosage compared with dosage 0,52 g/kgBB and 2,08 g/kgBB.